Pemberdayaan masyarakat dengan pelatihan pembuatan minuman kesehatan dari Tanaman Obat Keluarga (TOGA) - Erna Harfiani; Anisah Anisah; Agneta Irmarahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Health is important to maintain and prevents disease by maintaining health better than treating disease. Depok (West Java), is a fertile area but is quite densely populated, land for planting crops, including TOGA is limited. To motivate people to plant TOGA, training is needed to make health drinks to maintain daily health. Training in making health drinks can further motivate people to plant TOGA in the home yard. This training was preceded by counseling about TOGA and its benefits, especially turmeric (Curcuma domestica) and red ginger (Zingiber officinale L.). This training aims to make people understand more about the importance of planting TOGA, its use in maintaining daily health and being able to make health drinks that can prevent disease more than treat diseases, by consuming health drinks made independently. The results were the increasing knowledge of the community in RW 03 Depok Jaya Depok, about the importance of planting TOGA in the home yard and being able to make health drinks in the form of tamarind turmeric and red ginger powder.